2009
DOI: 10.1038/nrn2573
|View full text |Cite
|
Sign up to set email alerts
|

The locus coeruleus and noradrenergic modulation of cognition

Abstract: Mood, attention and motivation co-vary with activity in the neuromodulatory systems of the brain to influence behaviour. These psychological states, mediated by neuromodulators, have a profound influence on the cognitive processes of attention, perception and, particularly, our ability to retrieve memories from the past and make new ones. Moreover, many psychiatric and neurodegenerative disorders are related to dysfunction of these neuromodulatory systems. Neurons of the brainstem nucleus locus coeruleus are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
1,350
1
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,488 publications
(1,451 citation statements)
references
References 118 publications
43
1,350
1
11
Order By: Relevance
“…The hypothesis that the LC-NE system contributes to P3 generation during a target detection task is consistent with the allocation of attentional resources and arousal effects in humans [13,[17][18][19]. Monkey studies with the oddball paradigm have shown that the conditions for generating the P3 are highly similar to those for the LC phasic response: both are preferentially elicited by attended, task-relevant, arousing, and salient stimuli that are important for goal-directed behavior [15,20].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The hypothesis that the LC-NE system contributes to P3 generation during a target detection task is consistent with the allocation of attentional resources and arousal effects in humans [13,[17][18][19]. Monkey studies with the oddball paradigm have shown that the conditions for generating the P3 are highly similar to those for the LC phasic response: both are preferentially elicited by attended, task-relevant, arousing, and salient stimuli that are important for goal-directed behavior [15,20].…”
Section: Introductionsupporting
confidence: 52%
“…The P3 component is thought to originate from neuronal inhibitory signals that inhibit unrelated neural activity to promote processing efficiency of task-relevant stimuli, thereby yielding large P3 amplitudes [13]. Correspondingly, activation of the LC-NE system in response to an important stimulus sends a "network reset" signal to the brain that interrupts the activity of the ongoing functional networks and facilitates their reorganization to promote rapid behavioral adaptation [18,55]. It is probable that only in the group of responders, because of differences in network connectivity and interactions with other neuromodulators, the VNS-induced activation of the LC-NE system results in a stronger inhibition and network reorganization that causes the antiepileptic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the direct relationship of the FA to the axonal/microscopic organization within a voxel. FA in the basal forebrain tissue reflects cell bodies and axons, innervating axons of posterior brain regions such as the pons, as well as axons from the locus coeruleus which also pass through the basal forebrain en route to the cortex (Sara, 2009). In this tissue, a proportion of the axons, including cholinergic axons, are crossing over other axons.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that the neuromodulatory brainstem nucleus locus coeruleus (LC) is critical for the regulation of cognitive performance Kehagia, Murray, & Robbins, 2010;Sara, 2009;Yu & Dayan, 2005). The LC exhibits a strong phasic increase in activity during the processing of motivationally relevant stimuli, leading to the release of the neuromodulatory neurotransmitter norepinephrine (NE) in the hippocampus, neocortex, and many other projection areas.…”
Section: ) Introductionmentioning
confidence: 99%